2014
DOI: 10.14742/ajet.624
|View full text |Cite
|
Sign up to set email alerts
|

Exploring discipline differentiation in online discussion participation

Abstract: Online discussion forums are often the only interaction or communication a student in an online learning environment will have with the course instructor and fellow students. Discussion forums are intended to elicit a range of thinking skills from the students, from purely social interaction to metacognition in order to achieve deep learning. Given the increasing use of online learning environments, it is timely to question whether students from different disciplines use online discussion forums in different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The lack of confirmatory studies among the Australia-focussed articles could be explained by the fact that LMSs may have a more established presence in Australia than they do in China, and there is a greater need to explore the impact of these systems on specific situations and applications. Prominent examples in this review of LMS user-impact studies from Australia, include the study of online student attrition (Moore and Greenland 2017); Redmond, Devine, and Basson (2014)'s exploration of discipline differentiation in online discussion participation; and the paper by Sheridan, Kotevski, and Dean (2014) on learner perspectives of online assessments as a mechanism to engage reflective practice. The Chinafocused exploratory studies in this review also examined specific applications of LMS use from a user perspective, such as the study of online MBA programmes and their impact on working mothers (Kibelloh and Bao 2014); the investigation into integrating MOOC and flipped classroom practice in a traditional undergraduate course (Li et al 2015); and the study of e-learning privacy and personal information disclosure (Yang and Wang 2014).…”
Section: Exploratory Versus Confirmatory Designmentioning
confidence: 99%
“…The lack of confirmatory studies among the Australia-focussed articles could be explained by the fact that LMSs may have a more established presence in Australia than they do in China, and there is a greater need to explore the impact of these systems on specific situations and applications. Prominent examples in this review of LMS user-impact studies from Australia, include the study of online student attrition (Moore and Greenland 2017); Redmond, Devine, and Basson (2014)'s exploration of discipline differentiation in online discussion participation; and the paper by Sheridan, Kotevski, and Dean (2014) on learner perspectives of online assessments as a mechanism to engage reflective practice. The Chinafocused exploratory studies in this review also examined specific applications of LMS use from a user perspective, such as the study of online MBA programmes and their impact on working mothers (Kibelloh and Bao 2014); the investigation into integrating MOOC and flipped classroom practice in a traditional undergraduate course (Li et al 2015); and the study of e-learning privacy and personal information disclosure (Yang and Wang 2014).…”
Section: Exploratory Versus Confirmatory Designmentioning
confidence: 99%
“…Unfortunately, education is littered with technology systems that do not enhance teaching and learning, despite their promise (Cuban, Kirkpatrick, & Peck, 2001). Unreliable and difficult to use software systems often overwhelm even the most experienced educator and may frustrate any user (Cuban et al, 2001;Mishra & Koehler, 2006;Redmond et al, 2014;San Jose & Kelleher, 2009). Frustration often leads to users disengaging from or abandoning a system.…”
Section: The Usability Evaluation Of E-portfolio Systemsmentioning
confidence: 99%
“…Research has also identified that different e-portfolio systems vary in terms of level of robustness, ease of control, flow of information, and user interface (Balaban & Bubas, 2010;Buzzetto-More & Sweat-Guy, 2007;Shroff et al, 2011;Swan, 2009). In addition, users can be easily frustrated and discouraged when faced with a problematic user interface or ineffective technology system (Redmond, Devine, & Basson, 2014;San Jose & Kelleher, 2009). Student perspectives are often left out in higher education change management (Deneen, Brown, Bond, & Shroff, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The fourth is soft applied, which consists of education, law, and social sciences. The soft-applied disciplines focus more on the practical implementation of protocols or procedures (Redmond, Devine & Bassoon, 2014). Previous disciplinebased studies investigated student behaviors (Finnegan, Morris & Lee, 2008), instructional design of math courses (Smith, Torres-Ayala & Heindel, 2008), engagement of K-12 science classes (Jaber, Dini, Hammer & Danahy, 2018) and student performance and participation (Vo, Zhu & Diep, 2020).…”
Section: Introductionmentioning
confidence: 99%